INCREASING THE USE OF SOCIAL LEARNING NETWORK FOR STUDENTS OF SMP NEGERI 2 SYAMTALIRA BAYU REGENCY NORTH ACEH - T. Edyansyah; Juni Ahyar; Rico Nur Ilham; Irada Sinta; M.Subhan (RADJA PUBLIKA, 2023)
Nowadays the development of the internet is increasingly rapid and has penetrated into several fields, including education. Learning media is also developing and giving rise to Social Learning Networks. Edmodo is an online learning media that combines several Learning Management System and Social Network features into a Social Learning Network specifically created for educational purposes. To obtain an effective learning process, teachers and students must have innovative and interesting learning media, this is what was experienced by SMP Negeri 2 Syamtalira Bayu Kab. North Aceh. Teachers of SMP Negeri 2 Syamtalira Bayu Kab. North Aceh has carried out training to increase the use of Edmodo learning media, but students are still not using the Social Network-based learning media. This is the background for the service team to provide training on